Resisting Usefulness: Music and the Political Imagination - Ritchey, Marianna (Current Musicology, 2021)
Arts advocacy in the U.S. tends to cultivate state and philanthropic art support by emphasizing art’s potential to increase productivity and generate revenue in various ways. Even musicologists often take this rhetorical route, arguing for the continued relevance of our work, for example by noting that studying music cultivates the kind of creative thinking skills that make workers attractive to corporations like Google. This way of promoting music and musicology thus reinforces the logic of state and capital by demonstrating music’s usefulness within that logic. I argue that we should instead embrace and pedagogically center music’s uselessness as its most potentially radical quality. Doing so could help us construct a new political imaginary that might more robustly resist the antisocial logics of capital. My argument circles around the question of musical autonomy. While a certain version of autonomy undergirds our discipline’s tools and assumptions, today this value is dismissed by almost everyone, including leftists and liberals, activists and academics. In salvaging the autonomous ideal, I attempt to resituate it firmly within collective practice, an orientation it has traditionally been seen as transcending. My exploration of collective autonomy weaves together work from musicology, political theory, anthropology, feminist theory, and Black studies, as well as from radical activist traditions that develop outside of any institutional framework. I think with and through these diverse perspectives, arguing that celebrating music’s uselessness might aid our collective ability imagine a radically different world.